DESIGN AND CHARACTERIZATION OF PHOTONIC CRYSTAL FIBER FOR SENSING APPLICATIONS - Morshed, Monir; Arif, Md. Faizul Huq; Asaduzzaman, Sayed; Ahmed, Kawsar (European Scientific Journal, ESJ, 2015)
A simple structure of Photonic Crystal Fiber (PCF) for gas sensing and chemical sensing has been proposed in this paper. Index guiding properties of proposed PCF have been numerically investigated by using finite element method (FEM). From the numerical result, it is shown that the relative sensitivity and confinement loss depend on geomatrical parameters and wavelength. The relative sensitivity is increased by a increase of the diameters of central hollow core and innermost ring holes and confinement loss is decreased with a increase of the diameters of outermost cladding holes. By optimize the parmeters, the relative sensitivity is improved to the value of 20.10%. In this case, the confinement loss of the fiber is 1.09Ã—10-3 dB/m.